That Men May Live As Neighbors - Dow Chemical Company (1946)
Color print advertisement for Dow Chemical's Industrial Chemical Division. The advertisement features an illustrated scene of a city block. The accompanying text promotes the use of industrial chemicals for mass sanitation in "the modern city."
Keywords: Dow Chemical Company; Advertising; Chemical industry; Corporations; Sanitation; Sewage